"Bath Salts" Intoxication: A Case Report. (25th March 2012) - Falgiani, Michael; Desai, Bobby; Ryan, Matt
Abstract : We present a case of a potentially lethal ingestion of "Bath Salts." After presentation, we briefly review the epidemiology and pathology of "bath salts" ingestion.